Clarithromycin mitigates radiation pneumonitis in patients with lung cancer treated with stereotactic body radiotherapy - Takeda, Atsuya; Tsurugai, Yuichiro; Sanuki, Naoko; Enomoto, Tatsuji; Shinkai, Masaharu; Mizuno, Tomikazu; Aoki, Yousuke; Oku, Yohei; Akiba, Takeshi; Hara, Yu; Kunieda, Etsuo (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: Radiation pneumonitis is a critical pulmonary toxicity after irradiation of the lung. Macrolides including clarithromycin (CAM) are antibiotics. They also have immunomodulatory properties and are used to treat respiratory inflammatory diseases. Radiation pneumonitis has similar pathology to them. Adverse reactions to macrolides are few and self-limited. We thus administered CAM to patients with high-risk factors for radiation pneumonitis, and retrospectively investigated whether CAM mitigated radiation pneumonitis following stereotactic body radiotherapy (SBRT). Methods: Among consecutive patients treated with SBRT, we retrospectively examined lung cancer patients treated with a total dose of 40–60 Gy in 5–10 fractions and followed ≥6 months. Since January 2014, CAM has been administered in patients with pretreatment predictable radiation pneumonitis highrisk factors, including idiopathic interstitial pneumonias (IIPs), and elevated Krebs von den Lungen-6 (KL-6) and/or surfactant protein D (SP-D), and in patients developing early onset radiation pneumonitis. Results: Five hundred and eighty eligible patients were identified and divided into 445 patients during the non-CAM-administration era (non-CAM-era) (before December 2013) and 136 patients during the CAMadministration era (CAM-era) (after January 2014). Median follow-up durations were 38.0 and 13.9 months, respectively. The rates of radiation pneumonitis ≥ grade 2 and ≥ grade 3 were significantly lower in CAM-era (grade ≥2, 16% vs. 9.6%, P=0.047; grade ≥3, 3.8% vs. 0.73%, P=0.037). For patients with the pretreatment predictable high-risk factors, the rate of radiation pneumonitis ≥ grade 3 was significantly lower, and that of grade ≥2 had a lower tendency (grade ≥3, 7.2% vs. 0%, P=0.011; grade ≥2, 21% vs. 9.6%, P=0.061). For patients developing early onset radiation pneumonitis, the rate of radiation pneumonitis ≥ grade 3 was also significantly lower (23% vs. 0%, P